Glucagon-Like Peptide-1 Secreting L-Cells Coupled to Sensory Nerves Translate Microbial Signals to the Host Rat Nervous System - Buckley, Maria M.; O’Brien, Rebecca; Brosnan, Eilish; Ross, R. Paul; Stanton, Catherine; Buckley, Julliette M.; O’Malley, Dervla (Frontiers in Cellular Neuroscience, 2020)
An intact gut epithelium preserves the immunological exclusion of ‘non-self’ entities in the external environment of the gut lumen. Nonetheless, information flows continuously across this interface, with the host immune, endocrine and neural systems all involved in monitoring the luminal environment of the gut. Both pathogenic and commensal gastrointestinal bacteria can modulate centrally-regulated behaviours and brain neurochemistry and, although the vagus nerve has been implicated in the microbiota-gut-brain signalling axis, the cellular and molecular machinery that facilitates this communication is unclear. Studies were carried out in healthy Sprague Dawley rats to understand cross-barrier communication in the absence of disease. A novel colonic-nerve electrophysiological technique was used to examine gut-to-brain vagal signalling by bacterial products. Calcium imaging and immunofluorescent labelling was used to explore activation of colonic submucosal neurons by bacterial products. The findings demonstrate that the neuromodulatory molecule, glucagon-like peptide-1 (GLP-1), secreted by colonic enteroendocrine L-cells in response to the bacterial metabolite, indole, stimulated colonic vagal afferent activity. At a local level indole modified the sensitivity of submucosal neurons to GLP-1. These findings elucidate a cellular mechanism by which sensory L-cells act as cross-barrier signal transducers between microbial products in the gut lumen and the host peripheral nervous system.